2016
DOI: 10.1007/s00586-016-4914-5
|View full text |Cite
|
Sign up to set email alerts
|

Zero-profile anchored cage reduces risk of postoperative dysphagia compared with cage with plate fixation after anterior cervical discectomy and fusion

Abstract: Zero-profile anchored cage had a lower risk of postoperative dysphagia than cage with plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 49 publications
0
33
1
Order By: Relevance
“…McAfee [ 10 ] performed a prospective randomized on the same topic and draw the same conclusion. Xiao [ 11 ] found that Zero profile could reduce the incidence of postoperative dysphagia compared with ACDF. We also observed 4 anterior surgical plans, including ACDF, ACCF, ACCDF, and Zero profile.…”
Section: Discussionmentioning
confidence: 99%
“…McAfee [ 10 ] performed a prospective randomized on the same topic and draw the same conclusion. Xiao [ 11 ] found that Zero profile could reduce the incidence of postoperative dysphagia compared with ACDF. We also observed 4 anterior surgical plans, including ACDF, ACCF, ACCDF, and Zero profile.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that the incidence of dysphagia in the CP group was significantly higher than that in the ZP group at each follow-up time, which was consistent with previous studies. Xiao et al [30] The results of this study suggested that the ZP group was associated with a high incidence of subsidence, when compared with the CP group. Considering the different definitions of subsidence used in the above ten studies, we conducted subgroup analysis of subsidence defined as ≥ 2mm and subsidence defined as ≥ 3mm.…”
Section: Discussionmentioning
confidence: 56%
“…This theoretical advantage would also be present in disc arthroplasty because there is no instrumentation protruding from the spine. A recent meta‐analysis reported lower rates of dysphagia after 1 year in patients with zero‐profile plates compared to conventional ACDF plating . None of the ZTD patients with pharyngoesophageal perforations had zero‐profile implants, isolated corpectomy, or disc arthroplasty.…”
Section: Discussionmentioning
confidence: 99%